DRIS norms for cupuaçu trees cultivated in monocultures and in agroforestry systems - Dias, Jairo Rafael Machado; Perez, Daniel Vidal; Silva, Lucielio Manoel da; Lemos, Cleigiane de Oliveira; Wadt, Paulo Guilherme Salvador (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the performance of specific or generic DRIS norms regarding diagnosis of the nutritional state of cupuaçu (Theobroma grandiflorum) orchards, in Southwestern Amazonia. Cupuaçu leaf samples were collected from 153 commercial orchards with ages ranging from 5 to 18 years, cultivated either in monoculture or in agroforestry systems. Specific DRIS norms, obtained for each production system, and generic norms, for the entire population, were generated. DRIS norms were obtained considering the nutritional relationship between N, P, K, Ca, Mg, Fe, Cu, Zn and Mn. The majority of bivariate relation means between nutrients and diagnostics obtained from the specific DRIS norms did not differ in comparison to the ones obtained when the generic DRIS norm was used. The evaluation of the nutritional state of cupuaçu orchards can be done using generic DRIS norms, which do not take into account the production system.
Keywords: Theobroma grandiflorum; Amazonia; foliar diagnosis; nutritional state; fruit trees